Geomorphology of the Ubiñas Massif, Cantabrian Mountains, NW Spain (1:22,000) - Victoria Alonso (Journal of Maps, 2019)
A Geomorphological Map of the Ubiñas Massif, Cantabrian Mountains, at a scale 1:22,000 and covering 94.52 km2, is presented. The ‘Natural Park of Las Ubiñas-La Mesa’, a completely deglaciated glaciokarst, containing the highest peaks in this part of the Cantabrian Mountains, has been also declared ‘Biosphere Reserve’ by UNESCO. A previous geomorphological map (13.17 km2), recording glacial and periglacial, karst, slope, fluvial and anthropic features, is now enlarged to include the whole massif. An initial analysis of the present map, planned as a basic instrument to fulfil the needs of no particular end-users, provides information about rock avalanches during glaciation, preglacial deposits, and the absence of rock glaciers formed by calcareous debris, among other characteristics of the area. This cartography, considered as a fundamental base for environmental management, could be employed as a basis document to obtain other geomorphological derived maps.